2014
DOI: 10.1108/jcm-05-2014-0970
|View full text |Cite
|
Sign up to set email alerts
|

A matter of love: consumers’ relationships with original brands and their counterfeits

Abstract: Purpose – This paper aims to explore brand personality relationships in the context of original versus counterfeit products. Specifically, it investigates consumers’ perception of both original brands and their counterfeits. Design/methodology/approach – The authors present four studies conducted with 657 Mexican consumers who own or have owned an original luxury-brand product as well as a counterfeit of the same brand. Data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Alnawas and Altarifi (2016) made a similar recommendation for hotel brands, and Yannopoulou, Moufahim, and Bian (2013) found authenticity to be a key ingredient in Airbnb’s generation of brand love. In a study comparing consumers’ relationships with original brands and their counterfeits, Castaño and Perez (2014) found that consumers feel higher levels of love toward the original brands; consequently, they urged brand managers to emphasize issues of authenticity in order to encourage consumers to be faithful. Similarly, Riivits-Arkonsuo, Kaljund, and Leppiman (2014) highlight authenticity as one of the key elements of the brand experience that contributes to brand love, and subsequently, brand evangelism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alnawas and Altarifi (2016) made a similar recommendation for hotel brands, and Yannopoulou, Moufahim, and Bian (2013) found authenticity to be a key ingredient in Airbnb’s generation of brand love. In a study comparing consumers’ relationships with original brands and their counterfeits, Castaño and Perez (2014) found that consumers feel higher levels of love toward the original brands; consequently, they urged brand managers to emphasize issues of authenticity in order to encourage consumers to be faithful. Similarly, Riivits-Arkonsuo, Kaljund, and Leppiman (2014) highlight authenticity as one of the key elements of the brand experience that contributes to brand love, and subsequently, brand evangelism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Luxury products, in particular, are extremely susceptible to counterfeit manufacturers because of their high value and the perceived image of exclusivity (Phau et al, 2009). According to Carpenter and Edwards (2013), the causes for this abrupt rise in counterfeit products are: (a) accessibility of technology offering a variety of means to assemble superior value counterfeit products by replicating symbols and casings; (b) the globalization of the marketplace which makes the transportation of counterfeit products easier; (c) the manufacturing of genuine products in countries such as China, Egypt and Colombia, resulting in opportunities for the creation of counterfeits by local competitors via illegitimate channels; and (d) lack of legal penalties in a number of countries for producing counterfeits (Yoo andLee, 2009, Castaño andEugenia Perez, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They may form attachments with more than one brand in the same category (Fournier and Yao, 1997), or even with the original brands and their counterfeits (Castaño & Perez, 2014), as long as they are familiar with these brands. As it is the case for human relationships, bonds exist and flourish only for a brand consumers are familiar with.…”
Section: Brand Relationshipmentioning
confidence: 99%